Flue-gas and direct-air capture of CO2 by porous metal–organic materials. (13th January 2017) - Madden, David G.; Scott, Hayley S.; Kumar, Amrit; Chen, Kai-Jie; Sanii, Rana; Bajpai, Alankriti; Lusi, Matteo; Curtin, Teresa; Perry, John J.; Zaworotko, Michael J.
Abstract : Sequestration of CO2, either from gas mixtures or directly from air (direct air capture), is a technological goal important to large-scale industrial processes such as gas purification and the mitigation of carbon emissions. Previously, we investigated five porous materials, three porous metal–organic materials (MOMs), a benchmark inorganic material, Zeolite 13X and a chemisorbent, TEPA-SBA-15, for their ability to adsorb CO2 directly from air and from simulated flue-gas. In this contribution, a further 10 physisorbent materials that exhibit strong interactions with CO2 have been evaluated by temperature-programmed desorption for their potential utility in carbon capture applications: four hybrid ultramicroporous materials, SIFSIX-3-Cu, DICRO-3-Ni-i, SIFSIX-2-Cu-i and MOOFOUR-1-Ni ; five microporous MOMs, DMOF-1, ZIF-8, MIL-101, UiO-66 and UiO-66-NH2 ; an ultramicroporous MOM, Ni-4-PyC . The performance of these MOMs was found to be negatively impacted by moisture. Overall, we demonstrate that the incorporation of strong electrostatics from inorganic moieties combined with ultramicropores offers improved CO2 capture performance from even moist gas mixtures but not enough to compete with chemisorbents. This article is part of the themed issue 'Coordination polymers and metal–organic frameworks: materials by design'.